(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article reveals the conceptual foundations for implementing health-preserving educational technologies in the system of professional training for higher education students. It has been established that the culture of life safety is an integrative component of a specialist’s professional culture, which is formed gradually and requires purposeful pedagogical support. It has been found that the effectiveness of risk response depends on the level of development of relevant competencies, critical thinking, and self-regulation skills. The necessity of systematically using educational technologies aimed at harmonizing students’ physical, mental, and social health is emphasized. It is highlighted that health-preserving technologies are interdisciplinary in nature and include medical-hygienic, psychological-pedagogical, and social-adaptive components. The significance of using interactive methods as tools for strengthening psycho-emotional comfort in the academic environment is defined. It is noted that the effectiveness of implementing these technologies largely depends on the professional competence of the teacher and the institutional strategy of the higher education institution. It is emphasized that it is important to implement individualized educational pathways, taking into account the personal and professional characteristics of students. The need for continuous updating of curricula and modification of methodological materials according to current risks is stressed. It has been found that interactive technologies contribute to the development of tolerant communication skills, dialogical thinking, and self-awareness. The specifics of health-preserving technologies as means of preventing student burnout and overload are described. It has been clarified that physical activity should perform compensatory and preventive functions in the student community. The existence of obstacles to the implementation of health-preserving technologies, including cognitive overload, low physical activity, and non-compliance with healthy lifestyle principles, has been stated. The necessity of implementing a systematic monitoring of students’ health status throughout the entire period of study is defined. It is noted that the axiological component of the educational process forms the motivation to maintain health as a personal and social value. It is emphasized that creating a stable health-preserving educational environment is critically important for the comprehensive formation of life safety competencies.